2000
DOI: 10.1016/s0370-2693(99)01417-3
|View full text |Cite
|
Sign up to set email alerts
|

Monopoles in non-Abelian Einstein–Born–Infeld theory

Abstract: We study static spherically symmetric monopole solutions in non-Abelian Einstein-Born-Infeld-Higgs model with normal trace structure. These monopoles are similar to the corresponding solution with symmetrised trace structure and are existing only up to some critical value of the strength of the gravitational interaction. In addition, similar to their flat space counterpart, they also admit a critical value of the Born-Infeld parameter β.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…During the last months, there was a growing interest devoted to monopole and dyons, considered as classical solutions of the non-abelian Einstein-Born-Infeld-Higgs (EBIH) model [8][9][10]. This is motivated by the fact that the low energy effective action D-brane is related to a Born-Infeld model (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…During the last months, there was a growing interest devoted to monopole and dyons, considered as classical solutions of the non-abelian Einstein-Born-Infeld-Higgs (EBIH) model [8][9][10]. This is motivated by the fact that the low energy effective action D-brane is related to a Born-Infeld model (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Note that it is the symmetrized trace version of the theory which leads to the BPS equations coincident with the YMH ones. Effect of gravity on the NBI monopoles was discussed in 63,64 . Recently the NBI model with doublet Higgs was considered 65 , it was found that the sphalerons in this theory interpolate between the usual electroweak sphaleron and the NBI sphalerons of 56 .…”
Section: Nbi Monopolesmentioning
confidence: 99%
“…square root of a determinant, living inside higher dimensional worlds of branes. Addition of Higgs field and investigating its monopole solutions become equally attractive for the field theorists in the realm of confinement related problems [3]. We recall that the original BI electrodynamics was introduced in order to resolve the self-energy divergence in the Coulomb problem.…”
Section: Introductionmentioning
confidence: 99%